One-step rapid pyrolysis activation method to prepare nanostructured activated coke powder. (15th February 2020) - Fu, Jiapeng; Zhou, Binxuan; Zhang, Zhen; Wang, Tao; Cheng, Xingxing; Lin, Leteng; Ma, Chunyuan
Highlights: Activated coke powders is produced by one-step rapid pyrolysis activation method. Both pulverized coal and pine wood were used as feedstock. Properties of the derived activated coke powers were characterized in details. Steam affects coke's pore and surface depending on the use of parental material. Maximum pore volume and specific surface area reach 0.2373 cm 3 /g and 250.57 m 2 /g. Abstract: A one-step rapid pyrolysis activation method is proposed to produce activated coke powder (ACP) via a drop tube reactor by using pulverized Datong coal (DTC) and pine wood (PW) as feedstock. Small feedstock particle size, high heating rate, and effective activation agent, i.e., the mixture of oxygen and steam were arranged for the fast formation and development of various pore structure of ACPs. Detail characteristics of the ACP were investigated by using the nitrogen adsorption measurement, scanning electron microscope (SEM) and Fourier transform infrared spectrometer (FTIR) analysis. Results showed that the ACP presented well-developed nanostructure with considerable pore volume, specific surface area and surface functional groups. The pore volume and specific surface area of PWC-O6S10 could reach 0.2373 cm 3 /g and 250.57 m 2 /g. Activation atmosphere had played an important role to develop the pore structure and morphology of the ACP. Under 6 vol% oxygen concentration, the optimum steam partial pressure for micropore development of DTC was about 15 vol%, while it mostly promoted the growth of mesopores for PWC. All ACP samples presented variety of C/O/N containing surface functional groups, including OH, CH, CC, CO, CO, COC, CN, CN, etc., which remained relatively stable as the activation agents concentration changed.